The Distributional Consequences of Large Devaluations - Cravino, Javier; Levchenko, Andrei A. (American Economic Review, 2017)
We study the impact of large exchange rate devaluations on the cost of living at different points on the income distribution. Poor households spend relatively more on tradeable product categories and consume lower-priced varieties within categories. Changes in the relative price of tradeables and of lower-priced varieties affect the cost of living of low-income relative to high-income households. We quantify these effects following the 1994 Mexican devaluation and show that they can have large distributional consequences. Two years post-devaluation, the cost of living for the bottom income decile rose 1.48 to 1.62 times more than for the top income decile. (JEL D12, D31, E31, F31, O12, O19, O24)